PMRI-Based Teaching Materials Using the Context of Karate Sports in Elementary School Students during the COVID-19 Pandemic - Agnes Veronica; Melva Zainil; Yullys Helsa (JOURNAL OF TEACHING AND LEARNING IN ELEMENTARY EDUCATION (JTLEE), 2020)
The COVID-19 Pandemic has brought many obstacles for education in Indonesia. The learning process moves from school to learning at home. To increase students' interest in learning mathematics during the COVID-19 pandemic, it is necessary to design new innovations such as the use of the context of karate in mathematics learning. This study aims to develop learning materials using the context of karate based on Indonesian Realistic Mathematics Education with the topic arithmetic operations. This research is a development research using Plomp model. Three stages are used in the development of the Plomp model: 1) Initial research stage; 2) Prototype stage; 3) Assessment stage. In the initial stages, researchers conducted the data collection and gathered information through observation. In the second stage, the researcher designed the product and evaluated their validity through the expert team. In third stage, the researchers made a revision based on evaluation from the expert team and redo the validation assessment until the expert team states the product is valid for use in learning. Lesson plan of modules, teaching materials, and learning videos are stated valid with an average value of three validators 73.